Wound Healing and Omega-6 Fatty Acids: From Inflammation to Repair - Jéssica R. Silva; Beatriz Burger; Carolina M. C. Kühl; Thamiris Candreva; Mariah B. P. dos Anjos; Hosana G. Rodrigues (Mediators of Inflammation)
Wound healing is an evolutionarily conserved process that is essential for species survival. Wound healing involves a series of biochemical and cellular events that are tightly controlled, divided into 3 concomitant and overlapping phases: inflammation, proliferation, and remodelling. Poor wound healing or a chronic wound represents a silent epidemic that affects billions of people worldwide. Considering the involvement of immune cells in its resolution, recent studies are focused on investigating the roles of immune nutrients such as amino acids, minerals, and fatty acids on wound healing. Among the fatty acids, much attention has been given to omega-6 (ω-6) fatty acids since they can modulate cell migration and proliferation, phagocytic capacity, and production of inflammatory mediators. The present review summarizes current knowledge about the role of ω-6 fatty acids in the wound healing context.